2019
DOI: 10.4174/astr.2019.96.6.269
|View full text |Cite
|
Sign up to set email alerts
|

Visual and electrophysiological identification of the external branch of superior laryngeal nerve in redo thyroid surgery compared with primary thyroid surgery

Abstract: Purpose Thyroid reoperations are surgically challenging because of significant anatomical variance. Visual and functional identification of the external branch of the superior laryngeal nerve (EBSLN) were studied in 2 groups of patients who underwent primary and redo thyroid surgery. Methods This study was conducted on 200 patients: 100 patients with redo and 100 patients with primary thyroid surgery. In addition to visual identification, nerve branches were functionall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 30 publications
1
3
0
1
Order By: Relevance
“…In the present study, we achieved a 91% EBSLN exposure rate (61 in 67 nerves) based on visual exposure and confirmed that nerve function was good through the contraction of the cricothyroid muscle. This rate is satisfactory compared with those reported in previous studies with IONM (33)(34)(35).…”
Section: Discussionsupporting
confidence: 81%
“…In the present study, we achieved a 91% EBSLN exposure rate (61 in 67 nerves) based on visual exposure and confirmed that nerve function was good through the contraction of the cricothyroid muscle. This rate is satisfactory compared with those reported in previous studies with IONM (33)(34)(35).…”
Section: Discussionsupporting
confidence: 81%
“…We included these results in our study because in most cases, the EBSLN is approached before the VN and RLN, and we believe that IONM to protect the EBSLN is just as important as the RLN. Because IONM helps the visual and functional identification of the EBSLN and decreases the rate of EBSLN injury, the routine use of IONM for EBSLN is encouraged 31,32 …”
Section: Discussionmentioning
confidence: 99%
“… 24 Though the latest recommendation is to use an ‘intraoperative nerve monitor’ for locating and preserving these branches, the manoeuvre is of little help without in-depth knowledge of its relationships and known anatomical variations. 24 , 25 , 26 , 27 After arising from the inferior nodosum of the cranial nerve X at the level of the C2 cervical vertebra, the SLN runs down dorsal to the carotid sheath and bifurcates into two branches at around 1.5 cm from its origin and approximately 2.5 cm cranial to the carotid bifurcation. 1 , 5 , 24 The larger IBSLN runs downwards along the internal carotid artery and dorsal to it until it crosses the greater cornua of the hyoid bone.…”
Section: Discussionmentioning
confidence: 99%